Evaluasi Perencanaan dan Pengadaan Obat Antibiotik Berdasarkan Metode ABC Indeks Kritis di Instalasi Farmasi Rumah Sakit Robert Wolter Mongisidi Manado - Patricia Rosalind Moga; Widya Lolo; Gerald Rundengan (PHARMACON, 2022)
Planning and procurement of drugs is one of the activities in pharmaceutical services to avoid drug vacancies and therefore, it is necessary to concern with the control on the amount of drug using the ABC Critical Index method. The purpose of this study is to determine the percentage of antibiotics included in the ABC group based on the ABC Critical Index method at the Pharmacy Installation of Robert Wolter Mongisidi Hospital, Manado. This research is categorized as a quantitative descriptive one with retrospective data collection. Primary data is obtained from 28 respondents who fill out the questionnaire and secondary data is obtained from the Pharmacy Installation, Warehouse and Finance based on the documents on the use of antibiotic drugs from January to December 2021. The results indicates that group A containes 2 drug items (3,51%), group B contains 47 drug items (82,46%) and group C contains 8 drug items (14,04%). Therefore it is concluded that the group with the most items and the highest investment value is group B.